Investor Protection and Corporate Responsibility in Multinational Holding Bankruptcy: The Virtue Dragon Indonesia and China Case - Yuga Narazua Khanza (Jurnal Indonesia Sosial Sains, 2024)
This research examines the implications of holding company bankruptcy on subsidiaries in Indonesia, focusing on capital market law and investor protection. The bankruptcy of a holding company can lead to operational disruptions for its subsidiaries, affecting market confidence and devaluing investments. Investors in these subsidiaries may face risks of unfair treatment during the bankruptcy process. The study explores Indonesia's legal framework, including the bankruptcy law and regulations enforced by the Otoritas Jasa Keuangan (OJK), which are aimed at protecting investors' rights and ensuring transparency. The case of Virtue Dragon Indonesia, a subsidiary of a Chinese holding company, highlights the complexities of cross-border bankruptcy and the challenges of safeguarding minority investors. The research underscores the need for stronger legal protections for investors and suggests improvements in Indonesia’s capital market laws to enhance investor confidence and market integrity.